ответ: x>=-6 2x=15 3x>6
x=11+8 x=1 15:2 x=3*6
X=19 X=7,5 X=181/3x=1 -8x>-16 6,5x-2=<1,5x-1 2-3x=<x+6 5(x+1)-6<2,6 + x
1:1/3 -8:-8 4,5 = 1,5x -1=7x 5x+1-6<2,6 + x
x=3 X=1 X= 4,5:1,5 7:-1 0x<2,6 + x
X=7 X=2,6:0
X=0
3x-0,5 > 2(x-0,4)-x
2,5x > 1,6x
2,5:1,6
x=1,5625
Пусть x - n-й член прогрессии. Тогда с л.ч. стоит сумма первых n членов ар.пр., равная
(2a1 + d(n-1))/2 * n = (56.5 - 2.5n)n / 2 = (113 - 5n)n / 4
(113 - 5n)n / 4 = 157.5
113n - 5n^2 = 630
5n^2 - 113n + 630 = 0
D = 113^2 - 20 * 630 = 113^2 - 100 * 126 = 113^2 - (113 - 13)(113 + 13) = 13^2
n = (113 +- 13) / 10
n = 9 (второй корень нецелый)
x = 27 + 8 * (-2.5) = 27 - 20 = 7